Implementation of the Government Agency Performance Accountability System (SAKIP) Policy in the Central Aceh Regency Government - Wahyudi, Dedek; Aisyah, Siti; Khairani, Cut (Riwayat: Educational Journal of History and Humanities, 2025)
This research was conducted to analyze the implementation of the Government Agency Performance Accountability System (SAKIP) policy in the Aceh Regency Government. The problem of this research is the demand for bureaucratic reform that mandates all government agencies to achieve a minimum SAKIP implementation category of B or good, whereas the SAKIP implementation category of the Central Aceh Regency Government has not yet achieved a good score and is still in the CC category (less good). Additionally, the low accountability score of the Regency Government is accompanied by low results from the Integrity Assessment Survey (SPI), which is still in the vulnerable category, thereby impacting the high poverty rate in Central Aceh Regency and the failure to achieve regional macro indicators in improving community welfare. The research method used is descriptive qualitative, with research instruments being documentation studies and interviews. The research results show that the four aspects that must be met in the implementation of the SAKIP policy in the Central Aceh Regency Governmentnamely policy accuracy, implementation accuracy, target accuracy, and environmental accuracyare all inadequate. This is due to obstacles from interest factors, cultural factors, benefit principles, implementing apparatus factors, and budget factors, compounded by the lack of commitment from organizational leaders. The efforts made by the Aceh Tengah District Government to improve the implementation value of SAKIP include forming a district SAKIP team. The research recommendations suggest that the Aceh Tengah District Government should instruct regional apparatuses, within their authority, to formulate technical policies related to SAKIP, such as technical policies for performance planning, performance measurement, and performance reporting within the Aceh Tengah District Government. Additionally, they should enhance the quality of SAKIP implementation from the district government level to the regional apparatus in aspects of strategic planning, performance agreements, performance measurement, performance data management, performance reporting, as well as review and evaluation. They should set annual targets for improving SAKIP implementation by increasing coaching for the targeted regional apparatus to be ready to implement SAKIP more effectively at the district government level. Furthermore, they should improve public perception and community satisfaction by increasing the publication of all SAKIP documents through online media and providing online facilities for feedback and suggestions to enhance the district government's SAKIP. They should also improve the competence of implementing officials by conducting SAKIP-related training and increasing the budget for SAKIP socialization for all stakeholders, as well as conducting regular monitoring and evaluation of SAKIP based on the efforts made by all regional apparatuses.